2021
DOI: 10.1002/cpdd.971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postoperative Day and NR1I2 on Tacrolimus Clearance in Chinese Liver Transplant Recipients—A Population Model Approach

Abstract: We aimed to explore the new biomarkers influencing tacrolimus in vivo behavior in Chinese liver transplant recipients. A total of 418 drug concentration samples of 41 liver transplant patients were collected for modeling. A population pharmacokinetic model was developed using the nonlinear mixed-effects modeling approach. The potential covariates, such as postoperative day (POD), age, body weight, hepatic and renal function, and recipient genetic polymorphisms (ABCB1, CYP3A4, CYP3A5, NR1I2) were evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Another polymorphism is POR*28 , which was significantly associated with lower tacrolimus dose requirements and higher C 0 / D ratio in the first month post‐transplant 30,31,33 . Moreover, the gene NR1I2 has been shown to impact tacrolimus pharmacokinetics 32 . Variants in transporter genes ABCB1 and ABCC2 were associated with changes in tacrolimus pharmacokinetics in other studies 34,35,38 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another polymorphism is POR*28 , which was significantly associated with lower tacrolimus dose requirements and higher C 0 / D ratio in the first month post‐transplant 30,31,33 . Moreover, the gene NR1I2 has been shown to impact tacrolimus pharmacokinetics 32 . Variants in transporter genes ABCB1 and ABCC2 were associated with changes in tacrolimus pharmacokinetics in other studies 34,35,38 .…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have identified genetic variants other than those in CYP3A5 that could affect the tacrolimus pharmacokinetics 30–36 . CYP3A4 is increasingly being recognized as having an influence on tacrolimus pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the median postoperative LOS after LT at Mayo Clinic Hospital Arizona was 6 days, while median postoperative LOS after LT at UF Health Shands Hospital was 14 days. Compared with that in the United States, For example, a retrospective study from Beijing suggested that the median postoperative LOS after LT was 16 days (41). In addition, a retrospective study from Shanghai suggested that the median postoperative LOS after pediatric living donor LT was 24 days (42).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that in the United States, the median postoperative LOS after LT in China was relatively longer. For example, a retrospective study from Beijing suggested that the median postoperative LOS after LT was 16 days ( 41 ). In addition, a retrospective study from Shanghai suggested that the median postoperative LOS after pediatric living donor LT was 24 days ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths before 5 years of age have been estimated to 5.3 million globally in 2018, 47% of which occurred in the neonatal period (the first 28 days of life) [1]. In China, the neonatal mortality rate has been estimated at 4.5‰, accounting for nearly half of the under-five deaths [2]. To reduce preventable neonatal morbidity and mortality and improve women's and newborns' health, World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) jointly developed the Action Plan for Healthy Newborn Infants in the Western Pacific Region (2014-2020) which focused on delivery of early essential newborn care (EENC) [3].…”
Section: Introductionmentioning
confidence: 99%